Courtney Long: capstone - Long, Courtney, artist (Colorado State University. Libraries, 2019)
The artist's statement: Based on Sigmund Freud's theories of the unconscious mind, I have created a photographic representation of the invisible self. The unconscious mind creates connections in the brain that are inaccessible to our fluid stream of thought. It records data that influences us in behavior, thoughts and judgement. Freud theorized, like an iceberg, the most important part of the mind is below the surface. The series began during a three-week spree of dream states and nightmares. As a result, a period of contemplation and wonder of the subconscious surfaced in my work. These photos are what I have come imagine my unconscious mind to look like during nightly REM cycles.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Method: The photos were taken by turning off the lights in the studio, having the model dance and then opening the camera shutter. As the shutter remained open, I used a remote and popped a mono light as many times as I felt appropriate. I then closed the shutter and got my image.
Keywords: photography; photo image making